Methods of isolation and bioactivity of alkaloids obtained from selected species belonging to the Amaryllidaceae and Lycopodiaceae families - Dymek, Aleksandra; Mroczek, Tomasz (Current Issues in Pharmacy and Medical Sciences, 2021)
Alkaloids obtained from plants belonging to the Amaryllidaceae and Lycopodiaceae families are of great interest due to their numerous properties. They play a very important role mainly due to their strong antioxidant, anxiolytic and anticholinesterase activities. The bioactive compounds obtained from these two families, especially galanthamine and huperzine A, have found application in the treatment of the common and incurable dementia-like Alzheimer’s disease. Thanks to this discovery, there has been a breakthrough in its treatment by significantly improving the patient’s quality of life and slowing down disease symptoms – albeit with no chance of a complete cure. Therefore, a continuous search for new compounds with potent anti-AChE activity is needed in modern medicine. In obtaining new therapeutic bioactive phytochemicals from plant material, the isolation process and its efficiency are crucial. Many techniques are known for isolating bioactive compounds and determining their amounts in complex samples. The most commonly utilized methods are extraction using different variants of organic solvents allied with chromatographic and spectrometric techniques. Optimization of these methods and modification of their procedures potentially allows researchers to obtain the expected results. The aim of this paper is to present known techniques for the isolation of alkaloids, especially from three species Narcissus, Lycopodium and Huperzia that are a rich source of AChE inhibitors. In addition, innovative combinations of chromatographic and spectrometric methods and novel TLC-bioautography will be presented to enable researchers to better study the bioactivity of alkaloids.